PENERAPAN BUDAYA PERUSAHAAN DAN KINERJA KARYAWAN OUTSOURCING DALAM PERSPEKTIF HUKUM ISLAM - Dwi Sulistiani (El-QUDWAH, 2013)
PENERAPAN BUDAYA PERUSAHAAN DAN KINERJA KARYAWAN OUTSOURCING DALAM PERSPEKTIF HUKUM ISLAM   Oleh: Dwi Sulistiani Dosen Fakultas Ekonomi UIN Maulana Malik Ibrahim Malang Email: tiaraakbar2006@yahoo.com   Abstract: Widespread use of outsourced staff lately has many implications for the operations of the company. On the one hand, utilization of outsourcing makes companies more focused on its core business in order to improve efficiency. On the other hand, companies are faced with the fact that outsourced employees tend to have performance and loyalty are lower than permanent employees of the company itself. One of the factors that affect the performance and employee loyalty is their understanding of corporate culture and how they apply in their daily work. Outsourced employees often have greater difficulty to understand the culture in the company in which he is placed compared with permanent employees of the company sendiri.Kemudian how Islamic law view about it? The paper is literature review aims to determine the effect of the use of force against the application outsourcing company culture and employee performance. Based on various sources of reading, it can be concluded that there was indeed a lack of understanding of corporate culture trend by outsourcing employees so that their low performance and loyalty. But with the support of management and employees remain on the company where it is placed, undoubtedly outsourced employees can adapt and understand the corporate culture so well that the performance and loyalty increased.. Keyterm : Outsourcing, Corporate Culture, Performance, Perspective of Islamic Law